Strengthening of Character Through Boarding Based Lessons at SMK NU - Panggah Adi Putranto; Deni Setiawan (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This writing focuses on the application of the concept of Islamic boarding school-based learning strategies in formal schools. This study aims to describe the learning strategies based on Islamic boarding schools implemented in formal schools and generally private schools, including analyzing the aspects that contribute to implementing Islamic boarding school-based learning strategies. This research uses a descriptive qualitative approach. Data collection using observation and interviews, with data validity techniques using source triangulation. The study used 1,500 student informants at SMK NU, with interviews with 15 class teachers. The data collected is analyzed and described following the research consensus. The study results show that learning strategies based on Islamic boarding schools are implemented in formal schools without changing the education or office structure. This strategy prepares students to participate in learning activities with pleasure, and the end is happy from start to finish. The smooth running of lessons is backed by the cottage culture program. Supervising all students is very easy, mainly when it is supported by the location of school buildings in one area. In addition to the cottage program, there are also scholarship programs and orphanages. The intended scholarship program follows the capacity to memorize the Koran.